Consumption Response to Seoul's COVID-19 Shopping Coupons: Evidence from Consumer Data - Seokjin Woo; Sangmin Aum; Dohyung Kim; Heyjin Moon; Soohyung Lee (Institute of Labor Economics (IZA), 2021)
This study measures the extent to which Seoul's COVID-19 shopping coupon program affects individuals' consumption. Unlike other COVID-19-related transfer programs, the Seoul Metropolitan government provides consumption coupons depending on income. We quantify the causal effect of Seoul's program by comparing eligible and ineligible groups using a difference-in-differences method. We find that the program increased consumption by 18% while it was ongoing and by 6% afterward. We find substantial heterogeneity in the treatment effects concerning recipients' income and consumption categories.
Keywords: H2; H6; D3; D6; L1; 330; COVID-19; stimulus payment; consumption